An Alternative Approach to Treatment of Hypophosphatemia in Nonsurgical Critically Ill Patients in Countries With Limited Resources - Tijana Kovačević; Peđja Kovačević; Boris Tomić; Saša Dragić; Danica Momčičević (SAGE Publishing, 2019)
Background: Hypophosphatemia can complicate and prolong the treatment of critically ill patients, and it is even thought to be related to mortality rate. Objectives: The aim of this study is to determine whether using extemporary prepared phosphate buffer in pharmacy would help correct serum phosphate in critically ill patients. Methods: A prospective study was conducted at the medical intensive care unit over a period of 1 year and included 50 patients who were diagnosed with hypophosphatemia. Phosphate buffer was prepared at the pharmacy, and the dose range was recommended by a clinical pharmacist. Results: Patients were administered phosphate buffer via the nasogastric tube, and the doses chosen by the physicians depended on serum phosphate level and the severity of the patients' clinical status. Serum phosphate levels were successfully corrected in all treated patients. The most frequently used dose was 60 mmoL/d, and in most patients 1-day therapy was sufficient. No adverse effects were observed. Conclusion: The phosphate buffer is an adequate alternative for the treatment of hypophosphatemia of nonsurgically critically ill patients. One-day therapy with the 60 mmoL phosphate dose divided into 3 single doses resulted in normalization of serum phosphate values in most patients.